Peningkatan Nilai Impak Baja Hadfield Mn 12 Melalui Proses Perlakuan Panas Homogenisasi Bertahap - Ery Hidayat; Beny Bandanadjaja (Polinema Press, Politeknik Negeri Malang, 2018)
Hadfield manganese steel is the steel with a composition of 1.0-1.4% C and 10-14% Mn, where the C: Mn ratio is made at 1:10. In as-cast conditions, the steel has a structure of carbide (Fe, Mn) 3C at the grain boundary, formed during slow cooling in the sand mold. The carbide existence can cause brittle properties of the material and needs to be eliminated by a heat treatment process that is homogenization (or solution treatment). In this study, a stepped heat treatment process was carried out by giving preheating at temperatures below the austenitizing temperature of 600 oC and 700 oC. The austenitizing temperature is given lower than the conventional method which usually uses 1050 oC, wherein this study austenitizing heating was given at 980 oC. Rapid quenching is performed using water with agitation or stirring to ensure that the cooling rate is fast enough to generate a 100% austenite structure. The results achieved that the sample with a stepped heat treatment process with a preheating temperature of 600 oC and followed by austenitizing of 980 oC could perform finer austenite grains, with the highest impact value of 255 Joules. A fracture of the impact sample resulting very ductile behavior which can be seen that the impact sample is not completely broken.